Peripheral hypoarousal but not preparation-vigilance impairment endures in adhd remission - James, Sarah-Naomi; Brandeis, Daniel; Banaschewski, Tobias (Journal of attention disorders, 2017)
Objective: This study investigates whether impairments associated with persistent ADHD—impaired attention allocation (P3 amplitude), peripheral hypoarousal (skin conductance level [SCL]), and adjustment in preparatory state (contingent negative variation [CNV])—reflect enduring deficits unrelated to ADHD outcome or are markers of ADHD remission. Method: Young people with childhood ADHD (73 persisters and 18 remitters) and 144 controls were compared on neurophysiological measures during two conditions (baseline and fast-incentive) of a four-choice reaction time task. Results: ADHD remitters differed from persisters, and were indistinguishable from controls, on baseline P3 amplitude and fast-incentive CNV amplitude (p ≤ .05). ADHD remitters differed from controls (p ≤ .01), and were indistinguishable from persisters (p > .05), on baseline SCL. Conclusion: Preparation-vigilance measures were markers of ADHD remission, confirming previous findings with other measures. Yet, SCL-measured peripheral hypoarousal emerges as an enduring deficit unrelated to ADHD improvement. Future studies should explore potential compensatory mechanisms that enable efficient preparation-vigilance processes in ADHD remitters.
First published March 31, 2017
Gesehen am 10.07.2018